EFFECTIVENESS OF ANTISEPTIC BASED ON GANDARIA LEAVES (Bouea macrophylla Griff) ON THE GROWTH OF Staphylococcus aureus AND Escherichia coli - Lelapary, Claudia; Pattipeilohy, Mery; Mahulette, Ferymon (RUMPHIUS, 2022)
Gandaria leaves (Boea macrophylla Griff) have potential as antibacterial. The ability to inhibit bacterial growth is inseparable from the role of active compounds, namely flavonoids, tannins, quinones and triterpenoids. Growth by microbes needs to be controlled, namely by inhibiting microorganisms, one way is by using chemicals, namely antiseptics. This study aims to determine the effectiveness of antiseptics made from gandaria leaves against the growth of S. aureus and E. coli bacteria. The concentrations of the ethanol extract of gandaria leaves used were 5%, 15% and 25% and betadine (+) and aquades (-) were used as controls. Antiseptic effectiveness test against S. aureus and E. coli bacteria using disc diffusion method. The test results showed that the antiseptic based on gandaria leaves had the ability to inhibit the growth of S. aureus with a concentration of 15% at 2.00 mm and 25% at 4.00 mm. Meanwhile, for E. coli bacteria, antiseptic made from gandaria leaves has an inhibition zone at a concentration of 15% at 1.00 mm. In accordance with the criteria for antiseptic power according to Davis Stout, gandaria leaves which are used as basic ingredients for antiseptics are included in the criteria for very weak antiseptic power (≤5). Therefore, the antiseptic based on gandaria leaves in this study was less effective in inhibiting the growth of S. aureus and E. coli bacteria.